2008
DOI: 10.1080/13803390801992725
|View full text |Cite
|
Sign up to set email alerts
|

Measuring neuropsychological change following breast cancer treatment: An analysis of statistical models

Abstract: This article considers the quantitative techniques currently in use in the evaluation of cognitive impairments associated with chemotherapy treatment for breast cancer. To illustrate differences among analytical approaches, all analyses were applied to baseline and posttreatment scores on neuropsychological tests obtained from Stages I and II breast cancer patients receiving either chemotherapy or hormonal therapy; a healthy control group with similar demographics to those of the treatment groups was also incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 57 publications
2
58
0
1
Order By: Relevance
“…Furthermore, although results at the group level (e.g., statistical comparisons of group means) are very informative in studies of treatment effectiveness, they may also mask the variability in individual responses to interventions [70].…”
Section: Expert Commentarymentioning
confidence: 99%
“…Furthermore, although results at the group level (e.g., statistical comparisons of group means) are very informative in studies of treatment effectiveness, they may also mask the variability in individual responses to interventions [70].…”
Section: Expert Commentarymentioning
confidence: 99%
“…Slike testmetoder er ikke problemfrie, saerlig ved måling av individuelle endringer over tid (6). De fleste av testene har også svak sammenheng med dagliglivets problemer (7).…”
Section: Objektiv Kognitiv Dysfunksjonunclassified
“…Numerous studies have offered evidence for chemotherapy-induced adverse neuropsychological sequelae, independent of the effects of depression or anxiety, in the domains of memory, mental flexibility, processing speed, attention, visuospatial ability, and motor function [48][49][50][51]. These impairments are clinically significant, with pervasive impact on functioning in the home, social, educational, and/or professional environments [52]. Although research on outcomes of vitamin supplementation on chemotherapy-induced cognitive dysfunction is scant, one important study indicates a positive role of vitamin D. In a study of women with early-stage breast cancer who were being treated with chemotherapy, Simone et al [53] report that 88% of the sample indicated improvement in cognitive abilities after completion of a 10-point plan that included a supplement regimen high in vitamin D. Although additional research would be needed to isolate the contribution of vitamin D alone, these results show therapeutic promise for vitamin D in the context of chemotherapy-induced cognitive dysfunction.…”
Section: Vitamin D As An Agent For Cognitive Enhancementmentioning
confidence: 99%